Art, history, and the historiography of Judaism in Roman antiquity - Fine, Steven. (The Brill Reference Library of Judaism, 2014)
Art, History, and the Historiography of Judaism in Roman Antiquity explores the complex interplay between visual culture, texts, and their interpretations, arguing for an open-ended and self-aware approach to understanding Jewish culture from the first century CE through the rise of Islam. The essays assembled here range from the "thick description" of Josephus's portrayal of Bezalel son of Uri as a Roman architect through the inscriptions of the Dura Europos synagogue, Jewish reflections on Caligula in color, the polychromy of the Jerusalem temple, new-old approaches to the zodiac, and to the Christian destruction of ancient synagogues. Taken together, these essays suggest a humane approach to the history of the Jews in an age of deep and long-lasting transitions-both in antiquity, and in our own time. This book is also available in paperback. "Taken as a whole, Fine's book exhibits the value of bridging disciplines. The historiographical segments integrated throughout this volume offer essential insights that will inform any student of Roman and late antiquity." Yael Wilfand, Hebrew University , Review of Biblical Literature, 2014.